Top Secret. - Rosenwald, Michael (Columbia Journalism Review)
The article discusses the incidences of disinformation in the history of the U.S. The article reports that in early 2017, the U.S. government released findings from an investigation showing that Russian president Vladimir Putin, had ordered an unprecedented influence campaign. It mentions that the campaign involved disinformation and computer hacking.